Pregnancy-associated changes in peripheral blood lymphocyte subpopulations and serum cytokine concentrations in healthy women - Kumru, S; Boztosun, A; Godekmerdan, A (Sci Printers & Publ Inc, 2005)
OBJECTIVE: To investigate the effects of healthy pregnancy on peripheral blood T-cell subpopulations and serum T helper type 1 and 2 cytokines and transforming growth factor-beta 1 concentrations. STUDY DESIGN: Thirty healthy, pregnant women (study group, mean SD: 13 +/- 1.6 weeks of gestation) and 30 age-matched women with regular menstrual cycles (control group) participated in the study. Peripheral blood CD4(+), CD8(+) and CD16(+)56(+) (natural killer) percentages and serum interferon-gamma, interleukin-10 and transforming growth factor-beta 1 concentrations were measured by flow cytometry and enzyme-linked immunosorbent assay. RESULTS: In the study group, all pregnancies were maintained until term, no complications occurred, and the infants were delivered successfully. Although the percentage of CD4(+) T cells was not significantly different between the 2 groups, the percentages of CD8(+) T cells and natural killer cells were significantly increased (p < 0.05 for both), and the CD4(+):CD8(+) ratio was significantly decreased in the study group as compared to the control group (p < 0.05). Serum interferon-gamma concentrations were detectable in nonpregnant, nulliparous controls. However, pregnancy caused a severe decrease in serum interferon-gamma levels: they fell below the limit of detection. We also found increased serum interleukin-10 and transforming growth factor-beta 1 concentrations in the study group in comparison to the control group (p < 0.05). CONCLUSION: Healthy pregnancy causes immune deviation by increasing CD8(+) T and natural killer cells, serum interleukin-10 and transforming growth factor-beta 1 concentrations and decreasing the CD4(+):CD8(+) ratio.
Keywords: lymphocytes; pregnancy; cytokines; Turkey